Normal-Rayleigh Stochastic Production Frontier Model - S. Kannaki; L. Mary Louis (International Journal of Mathematics And its Applications, 2017)
In the production field, Stochastic Production Frontier Analysis (SPFA) plays a principal role in the measurement of technical efficiency. This paper presents the derivation of Normal-Rayleigh Stochastic Production Frontier Model (NRSPFM)for the estimation of technical efficiency. By using Maximum likelihood estimation method, the parameters of the model were evaluated.